Knowledge, attitude, and practice of blood donation: A cross-sectional survey in Khulna city, Bangladesh - Md. Salauddin Khan; Khondokar Naymul Islam; Sohel Rana; Nilay Kumar Sarkar (Elsevier, 2024)
Background: There is evidence that the worldwide need for safe blood is not being met, particularly in poor nations like Bangladesh, where there is a scarcity of voluntary blood donors. This research intends to evaluate the public's knowledge, attitude, and practice of voluntary blood donation and the socio-demographic factors associated with blood donation in Khulna city, Bangladesh. Materials and methods: 720 interviews were taken using a structural questionnaire with Khulna city residents implementing the convenience sampling technique. After pre-processing and removing missing values, 697 records were left for further analysis. To investigate the association of sociodemographic factors such as age, gender, education, occupation, marital status, permanent address, and smoking status with knowledge, attitude, and practice of blood donation, the binary logistic regression model was used. Results: According to this research, 478 (68.58%), 654 (93.83%), and 451 (64.71%) respondents were knowledgeable, had a favorable attitude, and practiced VBD, respectively. The study level higher secondary (AOR = 2.2; CI: 1.16-4.18), honors or degree (AOR = 2.37; CI: 1.3-4.3), and masters or above (AOR = 3.27; CI: 1.69-6.35) were associated with the knowledge. The favorable attitude was connected with being male (AOR = 2.24; CI: 1.23-4.06), learning about VBD through online social media (AOR = 2.61; CI: 1.13-6.05), and having knowledge of VBD (AOR = 3.05; CI: 1.82-5.12). Age between 26 and 35 years (AOR = 2.83; CI: 1.43-5.57) and older than 45 years (AOR = 3.74; CI: 1.34-10.4), being a man (AOR = 3.6; CI: 2.25-5.78), being a smoker (AOR = 1.87; CI: 1.17-2.98), knowing about VBD (AOR = 2.31; CI: 1.55-3.42), and having a positive attitude (AOR = 3.78; CI: 2.11-6.77) were significant factors for practicing blood donation. Conclusion: This research demonstrates poor blood donation practices and limited knowledge of blood donation among Khulna city residents. The awareness of the residents should be prolonged for voluntary blood donation by the health bureau, the government, and non-governmental organizations.